PENGGUNAAN DANA DESA DALAM PROGRAM PEMBERDAYAAN MASYARAKAT DI DESA TOUNELET I KECAMATAN SONDER (Use of Village Funds in Community Empowerment Programs in Tounelet I Village, Sonder District) - Gloria Lady Pangkey; Nordy F. L. Waney; Rine Kaunang (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2023)
The aim of the study was to determine the types of activities and the amount of allocation of funds financed by village funds both for physical programs and for empowerment programs in Tounelet Satu Village, Sonder District, Minahasa Regency. The research method used is a quantitative descriptive method followed by triangulation to verify program implementation and funding. The results of this study found that there were 20 types of programs that had been implemented for the form of community empowerment with 5 types of physical program activities and 15 types of community empowerment program activities with 11 types of social forms and 4 types of economic forms for the use of village funds that were used by 68.04 percent where for physical programs by 40.12 percent and community empowerment programs with 20.98 percent for economic form empowerment programs and 6.94 percent for social form community empowerment programs As well as community opinion regarding the suitability of the program and the use of funds as much as 66.67 percent of the community agree that there has been openness of the village government regarding village funds to community, 60.00 percent of the community agrees that the development program is in accordance with the use of village funds and as much as 66.67 percent of the community agrees that the development program is in accordance with village fund priorities.